Gender Differences in Semantic Fluency Patterns in Children - Soriano, Federico; Fumagalli, Julieta; Shalom, Diego; Juan Pablo Barreyro; Macarena Martínez-Cuitiño (East European Journal of Psycholinguistics, 2016)
Previous literature in cognitive psychology has provided data involving differences in language processing between men and women. It has been found that women are usually more proficient with certain semantic categories such as fruit, vegetables and furniture.  Men are reported to be better at other categories semantic, e.g.  tools and transport. The aim of this article is to provide an inquiry about possible differences in semantic category processing of living things (LT) and inanimate objects (IO) by Argentinian Spanish-speakers school-aged children. The group of 86 children between 8 and 12 years old (51.16% boys) has been assessed on a semantic fluency task. Six semantic categories have been tested, three of them from the LT domain (animals, fruit/vegetables, and body parts) and three from the IO domain (transport, clothes and musical instruments). Results showed differences in semantic processing between boys and girls. Girls retrieved more items from the LT domain and activated more animals and fruit/vegetables.  These findings appear to support an innate conceptual organization of the mind, which is presumably influenced by cultural factors and/or schooling.ReferencesAlbanese, E., Capitani, E., Barbarotto, R., & Laiacona, M. (2000). Semantic categorydissociations, familiarity and gender. Cortex, 36, 733–746.Barbarotto, R., Laiacona, M., & Capitani, E. (2008). Does sex influence the age of acquisitionof common names? A contrast of different semantic categories. Cortex, 44(9), 1161–1170. doi:http://dx.doi.org/10.1016/j.cortex.2007.08.016Capitani, E., Laiacona, M., & Barbarotto, R. (1999). Gender affects Word retrieval of certaincategories in semantic fluency tasks. Cortex, 35, 273–278. doi:http://dx.doi.org/10.1016/S0010-9452(08)70800-1Capitani, E., Laiacona, M., Mahon, B. Z., & Caramazza, A. (2003). What are the facts ofsemantic category-specific deficits? A critical review of the clinical evidence. CognitiveNeuropsychology, 20, 213–261. doi: http://dx.doi.org/10.1080/02643290244000266Caramazza, A., & Mahon, B. Z. (2003). The organization of conceptual knowledge: Theevidence from category-specific semantic deficits. Trends in Cognitive Sciences, 7, 354–361.Caramazza, A., & Mahon, B. Z. (2006). The organisation of conceptual knowledge in thebrain: the future’s past and some future directions. Cognitive Neuropsychology, 23, 13–38Caramazza, A., & Shelton, J. R. (1998). Domain-specific knowledge systems in the brain: Theanimate-inanimate distinction Journal of Cognitive Neuroscience, 10, 1–34. doi:http://dx.doi.org/10.1162/089892998563752Casals-Coll, M., Sánchez-Benavides, G., Quintana, M., Manero, R. M., Rognoni, T., Calvo, L.,& Peña-Casanova, J. (2013). Estudios normativos españoles en población adulta joven(proyecto NEURONORMA jóvenes): normas para los test de fluencia verbal. Neurología,28(1), 33–40.Fumagalli, J.; Sorinano, F.; Shalom, D.; Barreyro, J.P; Martinez Cuitiño, M.M (In press).Phonological and semantic verbal fluency task in a sample of Argentinean children. Temas emPsychologia, 25(3).Gainotti, G. (2005). The influence of gender and lesion location on naming disorders foranimals, plants and artefacts. Neuropsychologia, 43, 1633–1644. doi:http://dx.doi.org/10.1016/j.neuropsychologia.2005.01.016Gainotti, G., Ciaraffa, F., Silveri, M. C., & Marra, C. (2010). Different views about the natureof gender-related asymmetries in task based on biological or artefact categories. BehaviouralNeurology, 22(3–4), 81–90. doi: http://dx.doi.org/10.1155/2010/410858Gainotti, G., Spinelli, P., Scaricamazza, E., & Marra, C. (2012). Asymmetries in genderrelated familiarity with different semantic categories. Data from normal adults. BehaviouralNeurology, 27(2), 175–181. doi: http://dx.doi.org/10.1155/2013/138646Gerlach, C., & Gainotti, G. (2016). Gender differences in category-specificity do not reflectinnate dispositions. Cortex 85, 46–53.doi: http://dx.doi.org/10.1016/j.cortex.2016.09.022Hurks, P., Vles, J., Hendriksen, J., Kalff, A., Feron, F., Kroes, M., . . . Jolles, J. (2006).Category Fluency Versus Initial Letter Fluency Over 60 Seconds as a Measure of Automatic and Controlled Processing in Healthy School-aged Children. Journal of Clinical andExperimental Neuropsychology, 28, 284–295. doi: 10.1080/13803390590954191John, S., & Rajashekhar, B. (2014). Word retrieval ability on fluency task in typicallydeveloping Malayalam-speaking children. Child Neuropsychology: A Journal on Normal andAbnormal Development in Childhood and Adolescence, 20(2), 182–195. doi:http://dx.doi.org/10.1080/09297049.2012.760538Koren, R., Kofman, O., & Berger, A. (2005). Analysis of word clustering in verbal fluency ofschool-aged children. Archives of Clinical Neuropsychology, 20, 1087–1104. doi:http://dx.doi.org/10.1016/j.acn.2005.06.012Laiacona, M., Barbarotto, R., & Capitani, E. (2006). Human evolution and the brainrepresentation of semantic knowledge: Is there a role for sex differences? Evol. Hum. Behav,27, 158-168. doi: http://dx.doi.org/10.1016/j.evolhumbehav.2005.08.002Laws, K. R. (1999). Gender afects latencies for naming living and nonliving things:implications for familiarity. Cortex, 35, 729–733.Laws, K. R. (2000). Category-specificity naming errors in normal subjects: the influence ofevolution and experience. Brain and Language, 75, 123–133. doi:http://dx.doi.org/10.1006/brln.2000.2348Laws, K. R. (2004). Sex differences in lexical size across semantic categories. Personality andinvidual differences, 36, 23–32. doi: http://dx.doi.org/10.1016/S0191-8869(03)00048-5Leite, G., Pires, I., Aragão, L., Lemos, P., Gomes, E., Garcia, D., Barros, P., Alencar, J.,Fichman, H. & Oliveira, R. (2016). Performance of Children in Phonemic and SemanticVerbal Fluency Tasks. Psico-USF, 21(2), 293–304. https://dx.doi.org/10.1590/1413-82712016210207Lozano Guitiérrez, A., & Ostrosky-Solís, F. (2006). Efecto de la edad y la escolaridad en lafluidez verbal semántica: datos normativos en población hispanohablante. Revista Mexicanade Psicología, 23(1), 37–44.Mahon, B. Z., & Caramazza, A. (2003). Constraining questions about the organization andrepresentation of conceptual knowledge. Cognitive Neuropsychology, 20, 433–450.Marino, J., Acosta Mesas, A., & Zorza, J. (2011). Control ejecutivo y fluidez verbal enpoblación infantil: medidas cuantitativas,cualitativas y temporales. Interdisciplinaria, 28(2),245–260.Marino, J., & Díaz-Fajreldines, H. (2011). Pruebas de fluidez verbal categoriales, fonológicasy gramaticales en la infancia: factores ejecutivos y semánticos. Revista Chilena deNeuropsicología, 6(1), 49–56.Marra, C., Ferraccioli, M., & Gainotti, G. (2007). Gender-Related Dissociations of CategoricalFluency in Normal Subjects and in Subjects With Alzheimer’s Disease. Neuropsychology,21(2), 207–211. doi: http://dx.doi.org/10.1037/0894-4105.21.2.207Martínez-Cuitiño, M.; Shalóm, D.; Borovinsky, G.; Szenkman, D. & Fumagalli, J. (2014)¿Diferencias en el procesamiento semántico en niños en edad escolar? (77). Memorias delVI Congreso Internacional de Investigación y Práctica Profesional en Psicología, XXIJornadas de Investigación, décimo encuentro de investigadores en Psicología del Mercosur.Adicciones: Desafíos y perspectivas para la investigación.McKenna, P., & Parry, R. (1994). Category-specificity in the naming of natural and man-madeobjects. Neuropsychological Rehabilitation, 4, 255–281. doi: 10.1080/09602019408401461Moreno-Martínez, F. J., & Montoro, P. R. (2008). The impact of dementia , age and sex oncategory fluency: Greater deficits in women with Alzheimer’s disease. Cortex, 44,1256–1264.Moreno-Martínez, F. J. & Moratilla-Pérez, I. (2016). Naming and Categorization in HealthyParticipants: Crowded Domains and Blurred Effects of Gender. The Spanish Journal ofPsychology 19, 49, 1–15. doi:10.1017/sjp.2016.59Nieto, A., Galtier, I., Barroso, J., & Espinosa, G. (2008). Fluencia verbal en niños españoles enedad escolar: estudio normativo piloto y análisis de las estrategias organizativas. Revista deNeurología, 46(1), 2–6.Olabarrieta Landa, L., Benito Sanchez, I., Landa Torre, E., López Mugartza Iriarte, J., Alegret,M., Arango-Lasprilla, J. (2015) The Effect of Specific Language on Performance on VerbalFluency Tasks in Basque-Spanish Bilinguals. Arch ClinNeuropsychol, 30(6), 565. doi:10.1093/arclin/acv047.208Pekkala, S., Goral, M., Hyun, J., Obler, L. K., Erkinjuntti, T., & & Albert, M. (2009).Semantic verbal fluency in two contrasting languages. Clin Linguist Phon., 23(6), 431–445.doihttp://dx.doi.org/10.1080/02699200902839800Riva, D., Nichelli, F., & Devoti, M. (2000). Developmental Aspects of Verbal FluencyConfrontation Naming in Children. Brain and Language, 71, 267–284. doi:http://dx.doi.org/10.1006/brln.1999.2166Soriano, F., Fumagalli, J., Shalóm, D., Carden, J., Borovinsky, G., Manes, F., & MartínezCuitiño, M. (2015). Sex differences in a semantic fluency task. East European Journal ofPsycholinguistics, 2(1), 134–140.Spreen, O., & Strauss, E. A. (1998). Compendium of neuropsychological tests (2nd ed.). NewYork, NY: Oxford Univesity Press.Tulving, E. (1972). Episodic and semantic memory. In E. Tulving & W. Donaldson (Eds.),Organization Memory. New York: Academic Press.